Imagining Afghanistan in the aftermath of 9/11: conflicting literary chronographies of one invasion. Issue 1 (2nd January 2017) - Ivanchikova, Alla
ABSTRACT: After the end of the Cold War, the second world disappeared, and the post-socialist space became a silent non-region. A close look at representations of pre-war Afghanistan and more specifically representations of its socialist period in contemporary global Anglophone literature reveals a cartography of silences and evasions related to the difficulty of depicting socialism outside of the discourses of its historical failure. At the same time, examining and explicitly addressing these impasses presents a wealth of new possibilities for representation and articulation. In this paper, I discuss representations of the Soviet invasion in three Anglophone novels – Khaled Hosseini's The Kite Runner, M.E. Hirsh's Kabul, and Nadeem Aslam's The Wasted Vigil . These three texts, I argue, exemplify three divergent strategies of imagining Afghanistan's past, and consequently offer a path towards imagining its future as well as the future of the globe. I argue that representations of the Soviet invasion of 1979 serve as a pivotal lens through which the global community of readers is asked to understand the role of the US in contemporary geopolitical configurations, interpret the legacy of the Cold War, and evaluate the viability of alternative political projects in the twenty-first century – that is, it signals the way in which we make sense of our collective future.